Myasthenia Gravis Exacerbation Following COVID-19 Vaccine: A Case Report - Thoybah Yousif Ibrahim Gabralla; Hayat Abdoallah Ahmed Bashir; Omaima Abdalla Hajahmed Mohamed (University Library System, University of Pittsburgh, 2023)
Background: Vaccination remains the mainstay of strategy for prevention of Coronavirus Disease-2019 (COVID-19). AZD1222 (AstraZeneca vaccine) was distributed in Sudan by the COVID-19 Vaccines Global Access facility in March 2021. It was added to the emergency use list by the WHO in mid-February 2021. However, vaccine safety among patients with autoimmune diseases, such as myasthenia gravis (MG), is yet to be established. MG is a relatively rare illness that could result in life-threatening complications. Myasthenic crisis is considered the most serious complication of MG that can lead to death due to aspiration and respiratory failure. The case: We report the case of a 37-year-old Sudanese female who presented to the emergency room with an exacerbation of her normally well-controlled MG following her second dose of AZD1222 vaccination. She continued to deteriorate and was admitted to the intensive care unit, where she was intubated and placed on a mechanical ventilator. The low-income setting was a major barrier in obtaining intravenous immunoglobulin until the patient died. Our study aims to present an MG case with features of MG exacerbation following administration of a second dose of AZD1222. Conclusion: Little is known about the effect of different COVID-19 vaccines on subgroups of patients with autoimmune diseases like MG. In our case, an exacerbation of MG may have been precipitated by the COVID-19 AstraZeneca vaccine. Therefore, more efforts and experimental studies may be needed, with closer vigilance in MG patients